Causes and Measures to Control Root Rot Fungus in Mulberry Ecosystem - K Ramya Harika; Tejashree P; Karthick Mani Bharathi B; Susikaran S (International Journal of Fungi, 2024)
Root rot is a severe plant disease caused by various soil-borne fungi, including Phytophthora sp., Pythium sp., Rhizoctonia sp., Fusarium sp., and Armillaria sp. These pathogens attack plant roots, leading to decay, stunted growth, wilting, yellowing leaves, and plant death. Root rot typically develops in waterlogged soils with poor drainage, as these conditions create an environment favorable for fungal growth. Factors such as warm temperatures, compacted soil, improper watering practices, and plant stress (due to nutrient imbalances, mechanical injury, or weakened immunity) also contribute to the spread of root rot. Symptoms of root rot include root discoloration, a foul odor from decaying roots, and poor plant growth. Control measures focus on prevention through cultural, biological, and chemical strategies. Important cultural techniques include proper soil management and proper drainage. Crop rotation and the use of resistant plant varieties. Biological controls such as beneficial fungi (e.g., mycorrhizae) and antagonistic microbes (e.g., Trichoderma sp.) can help suppress fungal pathogens. Chemical treatments, including fungicides and soil fumigation, are used sparingly as a last resort. An integrated approach combining cultural, biological, and chemical methods is essential for long-term management of roots rot, thus ensuring the health and productivity of crops and plants.
Keywords: Bio-control; Host resistance; IPM; Root rot Fungus; management; symptoms